Revenge Concept as Manifested in Drawings and Narratives of Ultra-orthodox vs. Secular Israeli Jews - Lev-Wiesel, Rachel; Binyamini, Iris Manor; Schreiber, Michal Divon; Biran, Gideon; Estrin, Zohar; Goldstein, Gal; Shmerts, Nir Yosef; Nov, Shahar; Beja, Tali; Gallor, Maya; Sofer, Odeya Landesman; Miran, Lital; et al. (Journal of Urban Culture Research, 2023)
The current study investigates the revenge concept of ultra-orthodox and secular Israeli Jews, manifesting in drawings and narratives. The convenient sample consisted of thirty-three participants aged 23-61 (12 ultra-orthodox and 21 seculars). This mix-methodology study included the qualitative part, which are two sets of drawings and narratives – “draw an unjust event you experienced” and “draw what you would prefer to happen to the person who unjustly treated you;” and the quantitative part included a self-report questionnaire of the following measures: demographics, history of traumatic events, and feelings of injustice. Comparison between the two groups revealed no differences in the drawings and narratives, however, Orthodox Jews reported higher exposure to sexual abuse. The sexual abuse group showed a significant tendency to include words and physical touch between the victim and the perpetrator in the first drawing. A level of narrative organization was low in those with a history of sexual abuse.